Sex‐specific mediational effects of microglial activation on Alzheimer's disease proteinopathy in older adults. (20th December 2022) - Casaletto, Kaitlin B; Nichols, Emma; Aslanyan, Vahan; Simone, Stephanie M.; Rabin, Jennifer S.; La Joie, Renaud; Brickman, Adam M.; Dams‐O'Connor, Kristen; Palta, Priya; Kumar, Raj G.; George, Kristen M.; Satizabal, Claudia L; et al.
Abstract: Background: Women show disproportionate burden of Alzheimer's disease (AD) pathology and higher AD dementia prevalence compared to men, yet the mechanism(s) driving these vulnerabilities are unknown. There is sexual dimorphism in immunologic functioning and neuroimmune processes are implicated in AD genesis. Using neuropathology indicators from human brain tissue, we examined the mediational role of microglial activation on the relationship between amyloid and tau and how it differs by sex. Method: 187 decedents (64% female; 89 years‐old at death; 62% non‐demented) from the Rush Memory and Aging Project completed neuropathological evaluations with brain tissue quantified for microglial activation, amyloid‐β, and tau. Proportion of morphologically activated microglia was determined via immunohistochemistry (HLA‐DP‐DQ‐DR) and morphological staging (stage I, II, or III). Amyloid and tau burden were quantified via immunohistochemistry (M00872 or AT8, respectively). Using causal counterfactual modeling, we estimated the mediational effect of microglial activation on the amyloid to tau relationship in the whole sample and stratified by sex (amyloid→ microglial activation→ tau). Alternative models tested the role of microglia activation as the precipitating event (microglial activation→ amyloid→ tau). Result: Microglial activation significantly mediated 67% (95%CI 32‐90) of the relationship between amyloid and tau in the whole sample; however, stratified analyses suggested this effect was stronger and only statistically significant in women. 57% (95%CI 20‐100) of the effect of amyloid‐β on tau was mediated through microglial activation in women, compared to 19% (95%CI 0‐62) in men. Secondary models suggested that mediational effects were driven by cortical versus subcortical microglial activation. Alternative models suggested that in women, microglial activation was a significant exposure both preceding the amyloid‐β to tau relationship (50%, 95%CI 22‐89) and directly related to tau burden (50%, 95%CI 11‐78). In contrast, in men, only the direct effect of microglial activation to tau reached significance (74%, 95%CI 34‐99) (mediational effect: 25%, 95%CI 1‐66). Conclusion: Our models suggest a reciprocal, bidirectional relationship between amyloid‐β and microglial activation that accounts for tau burden in women. In men, direct independent (non‐mediational) relationships between microglial activation or amyloid‐β with tau were observed. Microglial activation may be disproportionately important for AD pathogenesis in women.